HUBUNGAN ANTARA KOHESIVITAS KELOMPOK DAN SIKAP PERAWAT PELAKSANA DENGAN PRODUKTIVITAS KERJA PERAWAT PELAKSANA DIRUANG RAWAT INAP RSUPN. DR. CIPTOMANGUNKUSUMO - Elsye Maria Rosa; Elly Nurachmah; Budiharto Budiharto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
Cooperation between the nursing team is a very important factor for achieving optimal quality of service. Teamwork in the hospital much influenced by the attitudes of nurses to perform nursing actions. The purposes of this study were to determine the relationship between group cohesiveness and the attitude of the nurse executive with labor productivity in RSUPN nurse executive Dr. Ciptomangunkusumo. The method of research is Deskriptive correlational, with cross sectionaldesign. The hypothesis of the study, relationship between group cohesiveness with the productivity of labor and the relationship between nurse executive position with the labor productivity of nurse executives. The results of bivariate statistical tests found that there were no relationship between group cohesiveness with the productivity of nurses working with a p-value executor 0.231, while attitudes have a significant association with work productivity perawata implementing the values of r = 0216, p-value 0.0007. Conclusion there was no significant relationship between group cohesiveness with the productivity of labor while a significant relationship between nurse executive with the work attitude of labor productivity in the inpatient nurses RSUPN. Cipto Mangunkusumo.